Frying properties of palm olein, canola oil, sesame oil and their blends - Serjouie, Alireza (2011)
Deep fat frying is a multifunctional procedure which is conducted by immersing awet product in a high-boiling-point liquid such as oil which causes all flavours and the juices to be retained by the crisp crust. This study was carried out to investigate the effect of frying on the physicochemical properties of refined, bleached, and deodorized (RBD) palm olein, canola oil and blends of palm olein, canola oil and/ or sesame oil during deep-fat frying (at 180°C) of potato chips for 3.5 h/d for five consecutive days in six formulations . The formulations were RBD palm olein (POo), canola oil (CO), RBD palm olein-sesame seed oil (POo:SO, 1:1), RBD palm oleincanola oil (POo:CO, 1:1), sesame seed oil-canola oil (SO:CO, 1:1) and RBD palm olein-sesame seed oil-canola oil (POo:SO:CO, 1:1:1). The frying oils were analyzed in terms of peroxide value (PV), -anisidine value (AV), iodine value (IV), free fatty acid (FFA) content, polymer content, total polar compounds, viscosity, TOTOX, E1% 1 cm at 233 and 269 nm, color, fatty acid composition, and C18:2/C16:0 ratio. In general, the results showed that there were significant (p < 0.05) differences among the proposed fried oils in terms of PV, AV, IV, FFA content, polymer content, viscosity, TOTOX, E1% 1 cm at 233 and 269 nm and color. In addition, the physicochemical analysis also showed that there were significant (P<0.05)differences in PV, AV, IV, FFA content, polymer content, viscosity, TOTOX, E1% 1 cm at 233 and 269 nm and color in each formulation during five consecutive days of frying (day 0 to 5) with some exceptions for E1% 1 cm at 233 nm observed in frying medium POo and yellow color in frying medium POo:SO and SO:CO within five different days of frying. As shown in this study, POo was the most stable frying medium, while CO was found to be an unstable frying oil due to the undesirable physicochemical changes that occurred after the frying process. In term of total polar compounds, the oil blend POo:SO:CO was shown to be the most stable frying medium among the six treatments. However, the oil blend POo:SO showed the better oxidative stability in term of PV. The fatty acid analysis showed that there was a decrease in both linolenic acid (C18:3) and linoleic acid (C18:2) contents. The chemical analysis exhibited that there was a significant (p < 0.05) difference among the six frying oils in terms of IV during five consecutive days of frying (day 0 to 5). Oil CO had the least stability in term of deep-fat frying due to high level of unsaturated fatty acids; conversely, oil blend POo:CO had the highest stability due to the lowest reduction in the C18:2/C16:0 ratio and IV. Considering what have been mentioned all above, it was concluded that POo was the best frying media. Although sesame oil has high level of natural antioxidants (phenolic compounds e.g., sesamin, sesamol, and sesamolin), it is more costly than POo and CO. In this study, oils blending helped to make frying oils more stable against the heating process without using any kind of chemical reactions such as hydrogenation, partial hydrogenation, interesterification, etc. Therefore, blended oil is economically option for frying process.Potato chips fried in POo and POo:SO:CO were chosen to be applied in the process of the accelerated storage test. All oils were separately utilized to fry the potato, then the potatoes were sampled and kept in eight metalized foil bags at 50 °C in an oven. Every five day for a period of 40 days, one of these bags was removed and PV, p-AV, TOTOX, TPC, colour, E1% 1cm at 233 and 269 nm and FACs tests were conducted on the oil extracted from the fried potato. Potato samples which were fried in POo:SO:CO oil had the highest stability in term of the change in FACs, reduction in C18:2/C16:0 ratio and yellow colour. In most analyses, the extracted oils had significant changes (p < 0.05) during the storage period. On the whole, it can be concluded that the potato samples fried in POo show the best stability in accelerated storage condition.